2016
DOI: 10.20546/ijcrbp.2016.306.002
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cytotoxicity and Antibacterial Evaluation of Aqueous, Methanolic and Ethanolic Extracts of Anastatica hierochuntica against Pathogenic Bacteria

Abstract: A b s t r a c t A r t i c l e I n f oThe cytotoxic effect of Anastatica hierochuntica was evaluated in vitro using Vero cell lines, characterized by identification of cellular alterations microscopically and cellular viability colorimetrically. The mean CC 50 value of methanol, ethanol, and aqueous extract were lower than 1000 µg/ml. The antibacterial activity of ethanol, methanol and aqueous extracts of A. hierochuntica was evaluated using agar well diffusion method against 10 bacterial pathogens. All the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Similarly, methanolic and ethyl acetate soluble fraction inhibited hepatotoxicity by 68.7% and 80.9% respectively, in a D-galactosamine-induced model ( Yoshikawa et al, 2003a ). AlSobeai (2016) demonstrated that the A. hierochuntica methanolic, ethanolic and aqueous extracts, tested at more than ≥1000 µg/ml, exerted no cytotoxic effects on a Vero cell line, providing evidence that it is only toxic to cancer cells. It was reasonable to study the antiproliferative activities of the aqueous and organic extracts of A. hierochuntica, considering the wide range of effective concentrations depending on the type of cancer cells and the duration of treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, methanolic and ethyl acetate soluble fraction inhibited hepatotoxicity by 68.7% and 80.9% respectively, in a D-galactosamine-induced model ( Yoshikawa et al, 2003a ). AlSobeai (2016) demonstrated that the A. hierochuntica methanolic, ethanolic and aqueous extracts, tested at more than ≥1000 µg/ml, exerted no cytotoxic effects on a Vero cell line, providing evidence that it is only toxic to cancer cells. It was reasonable to study the antiproliferative activities of the aqueous and organic extracts of A. hierochuntica, considering the wide range of effective concentrations depending on the type of cancer cells and the duration of treatment.…”
Section: Discussionmentioning
confidence: 97%
“…It is also important to note that the polar and non-polar phenolic compounds present in A. hierochuntica have been recently attributed to the nephroprotective, antioxidant and free radical scavenging activities [10]. The aqueous, ethanol and methanol extracts of A. hierochuntica have been shown to exhibit antibacterial activity against number of pathogenic bacteria which can lead to serious and life threatening complications such as sepsis, kidney and liver failure, toxic shock, and even death if it untreated [11].…”
Section: Introductionmentioning
confidence: 99%